Cancer incidence and cancer control in Bangkok, Thailand: Results from the cancer registry 2011-15 and projections to 2035. (August 2020) - Sangrajrang, Suleeporn; Laversanne, Mathieu; Bausom, Rangsiya; Mery, Les; Bray, Freddie
Highlights: The five most frequent cancers in Bangkok comprise 60 % of the burden in both sexes. In males, cancers of the lung, liver and colorectum each comprised 14–16 %. In females, breast cancer was responsible for almost 30 % of cancers in women. Demographic changes mean that the burden will rise over the next two decades. Abstract: Background: With considerable diversity in the patterns of cancer in different regions of Thailand and between urban vs. rural areas, this report focuses on cancer incidence burden in the Bangkok Metropolis 2011−15. Methods: Incidence rates in Bangkok were derived as the mean annual number of new cancer cases per 100, 000 inhabitants for the period 2011–2015 stratified by 5-year age group and sex. Age-standardized incidence rates (ASR) were calculated using the world standard population. Results: The five most frequent cancers in Bangkok correspond to close to 60 % of the total burden in both males and females. In males, cancers of the lung, liver and colorectum each comprised 14–16 % of the burden, while breast cancer was responsible for three in 10 cancers in women (or 29.4 %), with colorectal and cervical cancer ranking second and third (10.0 % and 8.5 % respectively). respectively. Under three different scenarios of trends in all-cancer incidence rates, demographic changes mean that the incidence burden will rise over the next two decades. Conclusions: The critical relevance of this information in the context of the planning and evaluation of national cancer control policies in Thailand is discussed. Evidently, the Bangkok and other Thai population-based cancer registries are essential in measuring the population-level impact of tobacco control, HBV and HPV vaccination, cervical and colorectal cancer screening, and via survival estimation, the effectiveness of cancer care.